PETROGRAFIA E LITOQUÍMICA DO MAGMATISMO TARDI-OROGÊNICO TOLEÍTICO ALTO-K E DA SUÍTE PÓS-COLISIONAL ALCALINA SATURADA EM SÍLICA DE GOUVEIA (MG) - Chaves, Alexandre de Oliveira; Coelho, Raphael Martins; Renger, Friedrich Ewald; Dussin, Tania Mara; Azevedo, Maria do Rosário Mascarenhas de Almeida; Ribeiro, Sara Monteiro (Geochimica Brasiliensis, 2015)
Close to Gouveia town (MG) and located inside granitoids and gneiss of the Gouveia Complex, porphyritic latites (or trachy-andesites) slightly metamorphosed are identified, with plagioclase and sanidine phenocrysts and matrix also feldspar-rich containing biotite, magmatic epidote and quartz. Occurring adjacent to the porphyrites, metamorphosed phanerites also appear, with terms ranging from ultramelanocratic lamprophyres (rich in amphibole and phlogopite with interstitial microcline), melanocratic monzonites (or syeno-diorite with hornblende, biotite, microcline and plagioclase), mesocratic syenites up to leucocratic quartz-syenites (with microcline, biotite and quartz). Lithochemistly, porphyrites and phanerites are metaluminous rocks, however the porphyrites are subalkaline, high-K tholeiitic and tardi-orogenic, while phanerites comprise a silica-saturated alkaline shoshonitic magmatic suite, called Gouveana Suite, whose lithotypes are genetically interrelated by magmatic fractionation processes occurred during an episode of post-collisional uplift. Apparently derived from distinct mantle sources, porphyrites and phanerites should be tectonically associated to regional transcurrent faults at the end of either Transamazonic or Brasiliano Events.